KINERJA DINAS PERTANIAN DALAM MENINGKATKAN BERAS LOKAL DI KABUPATEN BENGKULU SELATAN - Moh Ferro Zazili; Rekho Adriadi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
The performance of an organization is the result of a combination of capabilities, efforts, and opportunities that can be evaluated through its work results. Optimal performance is achieved through a combination of various factors that support the achievement of goals, such as human resource management (HR). These factors include adequate capabilities, high work enthusiasm to achieve organizational targets, and the ability to utilize existing opportunities to increase the value of the work done. Rice as a source of rice is the staple food for the majority of Indonesian people. Although it can be replaced by other foodstuffs, rice has a special value for those who are accustomed to eating rice, making it difficult to replace. However, the availability of food every year shows an increasing gap between the growth of rice production and the increase in population, which is often not in line. The purpose of this study based on the formulation of the problem is to Analyze the Performance of the Agriculture Service in Increasing Local Rice in South Bengkulu Regency. The performance of the Agriculture Service refers to the success of the government agency in achieving the goals and objectives that have been set, especially in increasing agricultural production, farmer welfare and food security. This refers to various aspects, ranging from planning, implementation, to evaluation of programs and activities in the agricultural sector. In the context of the performance of the South Bengkulu Regency Agriculture Service, it cannot be said to be able to meet the existing indicators, this is because the performance of the South Bengkulu Agriculture Service has not been achieved perfectly, because there is still a decline in agricultural output due to the narrowing of agricultural land because it is used as a residential area, but when viewed from the area of ​​agricultural land and the results obtained, it can still be said to be good, but when compared to the results each year there is a decline, but apart from that the performance of the Agriculture Service can be said to be good. Keywords: Performance, Department of Agriculture, Local Rice